Attaining Effectiveness in Primary Education in Kwara State through School-Based Management - Iliyas, R. A.; Alabi, M. B. (International Journal of Educational Management, 2022)
This paper on School Based Management (SBM) and attaining effectiveness in primary education in Kwara State has attempted an expository foray on the SBM. It explains the concept SBM, clarifies its model and types and the conceptual framework supporting the innovative management strategy is enunciated. The paper as well examines fundamental functions of SBM wherever it is said to be introduced from the very general functions to the more ambitious and rarely allowed ones. In the same connections, the paper, from interactions with stakeholders where SBM is in operation in Kwara State, attempts an ex-ray of how, what and who of the SBM. A balanced SBM is identified with the type in Kwara and it is observed that the type in operation in Kwara is the very weak type that nearly all components involved in it do not seem to clearly have a good grasp of what SBM should serve. Some recommendations offered in this paper include among others an obligatory need to define and educate various segments in the SBM Committee on the objectives of the management strategy; and to eliminate characteristic Nigerian redtapism, an enabling act of parliament would be necessary to delineate roles and empower the SBM operation in the State as strengthening measures and as a way of curbing manipulations.